Exploration and Analysis of Resource Scheduling and Management Mode in Future Space TT＆C Network - Hong ZHANG; Jia XUE; Bo REN; Xiaojun DU; Meng XUE (天地一体化信息网络)
The running mode and existing issues of current resource scheduling system operation model of TT＆amp;C network were discussed firstly.Then the development trends of future resource scheduling and management models were summarized, included integration of data transmission, automation of system operation, intelligence of algorithm allocation, coexistence of random access and pre-allocation.In the end, accorded to the management demands of integration, automation and intelligentization, the operating framework of the future resource scheduling model was put forward.After that, the key technologies which need to be broken through of the framework were researched deeply.And the further construction object of resource scheduling research was proposed in order to provided a reference for subsequent engineering applications.